Effects of carbonaceous impurities on the electrochemical activity of multiwalled carbon nanotube electrodes for vanadium redox flow batteries. (May 2018) - Mustafa, Ibrahim; Al Shehhi, Asma; Al Hammadi, Ayoob; Susantyoko, Rahmat; Palmisano, Giovanni; Almheiri, Saif
Abstract: The presence of impurities within multiwalled carbon nanotubes (MWCNTs) have major, but as-yet-unrecognized, effects on the electrochemical behavior of MWCNTs in vanadium redox flow batteries. We show that MWCNTs constitute a high-surface-area, electrically conductive, inactive carbon matrix that acts as a bridge between and a support for carbonaceous impurities that are highly active toward the VO 2+ /VO2 + redox couple. We use freestanding sheets of MWCNTs, either purified and subsequently not modified with impurities (pure) or purified and subsequently contaminated with carbonaceous impurities (impure), as electrodes to eliminate the need for a substrate and thus undesired mixed kinetics. Electrodes fabricated with pure MWCNTs show low activities; attributed to relatively inactive basal sites. In contrast, impure electrodes show high activities due to the increased number of defects and edge sites resulting from the presence of the impurities. Functionalization of pure MWCNTs surface with oxygen-containing groups substantially improve the activity of the electrodes. However, functionalization is not as effective when carbonaceous impurities are present. The carbonaceous impurities form a continuous debris layer over the nanotube fibers, which reduces the effect of the oxidation treatment. Our results indicate that the impurity content of MWCNTs should be considered in studies of their activity and functionalization. Graphical abstract: Image 1